Designing for effective controlled release in agricultural products: new insights into the complex nature of the polymer–active agent relationship and implications for use. (22nd June 2020) - Levett, Ian; Liao, Minjie; Pratt, Chris; Redding, Matthew; Laycock, Bronwyn; Pratt, Steven
Abstract: BACKGROUND: Various active chemical agents, such as soil microbial inhibitors, are commonly applied to agricultural landscapes to optimize plant yields or minimize unwanted chemical transformations. Dicyandiamide (DCD) is a common nitrification inhibitor. However, it rapidly decomposes under warm and wet conditions, losing effectiveness in the process. Blending DCD with an encapsulating polymer matrix could help overcome this challenge and slow its release. Here, we encapsulated DCD in a biodegradable matrix of poly(3‐hydroxybutyrate ‐co‐ 3‐hydroxyvalerate) (PHBV) and investigated the effects of DCD crystal size and loading rates on release rates. RESULTS: Three DCD crystal size fractions (0–106, 106–250 and 250–420 μm) were blended with PHBV at 200, 400, 600 and 800 gkg −1 loadings through extrusion processing and release kinetics were studied in water over 8 weeks. For loadings ≥ 600 g kg −1, more than 95% release was reached within the first 7 days. By contrast, at 200 g kg −1 loading only 10%, 36% and 57% of the DCD was mobilized after 8 weeks in water for 0 to 106 μm, 106 to 250 μm and 250 to 420 μm crystal size fractions, respectively. CONCLUSION: The lower percolation threshold for this combination of materials lies between 200 and 400 g kg −1 DCD loading. The grind size fraction of DCD significantly affects the quantity of burst release from the surface of the pellet, particularly below the lower percolation threshold. The results presented here are likely translatable to the encapsulation and release of other crystalline materials from hydrophobic polymer matrices used in controlled release formulations, such as fertilizers, herbicides and pesticides. © 2020 Society of Chemical Industry